PENGARUH PROFIT, TOTAL ASET, DAN TOTAL HUTANG TERHADAP EFFECTIVE TAX RATE PADA PERUSAHAAN INFRASTRUKTUR DI INDONESIA - Dewi Ratna Prihaningtyas; Aris Soelistyo; Muhammad Faisal Abdullah (Jurnal Ilmu Ekonomi JIE, 2018)
This research is aimed to find out the effect of profit, asset total, and debt total to the Effective Tax Rate of registered infrastructure company in Indonesia Stock Exchange in the period 2012-2016. Profits, assets total, and debt total as independent variable. The samples determined by purposive sampling method, and there are 15 infrastructure companies that fulfilling the criteria. Data analysis done by panel regression and using Eviews9. The result of this research shows that profit, assets total, and debt total are having simultaneously significant impact to ETR. While partial profit has positive and significant impact to ETR. Assets total has negative and significant to ETR. And debt total has positive and significant to ETR.Keywords: Tax Expense, Profit, Assets Total, Debt Total